Evaluating Nighttime Governance Structures: Implications for Urban Policy in Night Mayor and Consultative Body Models - Mohamed H.Mahmoud; Piotr Zmyślony (Studia Periegetica)
The rise of night mayors and other nighttime governance bodies represents an emerging model of urban governance. Vibrant nightlife scenes have become central to the identity and economy of global cities. However, the complex needs of nightlife stakeholders pose unique governance challenges. In response, some cities have instituted specialized offices of night mayor to oversee nighttime economic policy. This goal of this article is to examine this solution as a unique governance approach and compare the roles of night mayors to other nighttime consultative bodies like councils, commissions, panels, and boards. Taking into account all kinds of utility derived from nighttime activities, externalities, and stakeholders needs, the author differentiates night mayors’ concentrated leadership from the broader representation of advisory panels. It turns out that night mayors provide centralized oversight, while councils offer grassroots expertise. By working together they can create holistic strategies tailored to nighttime economies.